Influence of subgrade filling types on covering effect in seasonally frozen soil area - FENG Degang; HAO Dongmiao; ZHANG Mingli; YAN Yanfeng; ZHOU Zhixiong; ZHANG Ruiling; LI Guang (Shenzhen Daxue xuebao. Ligong ban)
The existence of a large area of expressway pavement in seasonally frozen soil region causes the moisture in roadbed filler to migrate upward and accumulate under the action of external temperature gradient and road barrier which aggravates the frost heave and thaw settlement of the subgrade. The formation process of subgrade covering effect in seasonally frozen soil area is reproduced by laboratory experiment. The water-vapor-heat model of unsaturated soil is established to simulate the formation process and difference of different subgrade filling cover effect in a certain area of Lanzhou. The results show that under the effect of seasonal temperature changes， soil water accumulates to the bottom of the impervious layer， and the accumulation phenomenon intensifies with freezing-thawing cycles. When the subgrade fillings are sandy soil， silty soil and silty clay， the maximum frozen depths are 1.21， 0.97 and 0.89 m， respectively， due to the difference in thermal conductivity and soil moisture diffusivity of the fillings. Water vapor migration dominates the water transport in shallow ground， which is most significant in silty soil. Water accumulations of sandy soil， silty clay and silty soil subgrade are 0.68%， 2.86% and 12.56%， respectively. The accumulation depth becomes shallower in turn. It is important to prevent and control the subgrade hazards caused by water vapor migration in the existing subgrade engineering.